(untitled) (Journal of the College of Basic Education, 2023)
By syllabic poetry, we mean that in which the rhyme changes and takes place according to binary or triple syllables ormore, and some of its patterns (such as double and straight) appeared (1) since an advanced period in the history of poetry.The Arab *, despite the fact that these two styles, in spite of the abundance of regulation in them over time and the circulation ofThe ages did not add to them that many new things, rather they receded greatly. (The double) has shortened itPoets for educational and governmental purposes are committed to it in the sea of ugliness, as it allows the abundance of its creeps and its causesHe composed tall tales and pure sciences, and did not go back to the well-known purposes of Arabic poetry.During the description and expulsion, as for (Al-Musmat), the attempts of the poets in it were limited to the purposes ofSentimental and perhaps the position of the old critics who rejected such two patterns had a great impact ontheir end to what we found them in the modern era.